International collaborative study to assess cardiovascular risk and evaluate long‐term health in cats with preclinical hypertrophic cardiomyopathy and apparently healthy cats: The REVEAL Study. (16th April 2018) - Fox, Philip R.; Keene, Bruce W.; Lamb, Kenneth; Schober, Karsten A.; Chetboul, Valerie; Luis Fuentes, Virginia; Wess, Gerhard; Payne, Jessie Rose; Hogan, Daniel F.; Motsinger‐Reif, Alison; Häggström, Jens; Trehiou‐Sechi, Emilie; et al.
Abstract : Background: Hypertrophic cardiomyopathy is the most prevalent heart disorder in cats and principal cause of cardiovascular morbidity and mortality. Yet, the impact of preclinical disease is unresolved. Hypothesis/Objectives: Observational study to characterize cardiovascular morbidity and survival in cats with preclinical nonobstructive (HCM) and obstructive (HOCM) hypertrophic cardiomyopathy and in apparently healthy cats (AH). Animals: One thousand seven hundred and thirty client‐owned cats (430 preclinical HCM; 578 preclinical HOCM; 722 AH). Methods: Retrospective multicenter, longitudinal, cohort study. Cats from 21 countries were followed through medical record review and owner or referring veterinarian interviews. Data were analyzed to compare long‐term outcomes, incidence, and risk for congestive heart failure (CHF), arterial thromboembolism (ATE), and cardiovascular death. Results: During the study period, CHF, ATE, or both occurred in 30.5% and cardiovascular death in 27.9% of 1008 HCM/HOCM cats. Risk assessed at 1, 5, and 10 years after study entry was 7.0%/3.5%, 19.9%/9.7%, and 23.9%/11.3% for CHF/ATE, and 6.7%, 22.8%, and 28.3% for cardiovascular death, respectively. There were no statistically significant differences between HOCM compared with HCM for cardiovascular morbidity or mortality, time from diagnosis to development of morbidity, or cardiovascular survival. Cats that developed cardiovascular morbidity had short survival (mean ± standard deviation, 1.3 ± 1.7 years). Overall, prolonged longevity was recorded in a minority of preclinical HCM/HOCM cats with 10% reaching 9‐15 years. Conclusions and Clinical Importance: Preclinical HCM/HOCM is a global health problem of cats that carries substantial risk for CHF, ATE, and cardiovascular death. This finding underscores the need to identify therapies and monitoring strategies that decrease morbidity and mortality.